Steel Fiber Enhancement upon Punching Shear Strength of Concrete Flat Plates Exposed to Fire Flame - Dalaf, Ahmed Naji; Mohammed, Shatha Dheyaa (Salehan Institute of Higher Education, 2021)
In this study, the effect of fire flame on the punching shear strength of steel fiber reinforced concrete flat plates was experimentally investigated using nine half-scale specimens with dimensions of 1500×1500 mm and a total thickness of 100 mm. The main investigated variables comprised the steel fiber volume fraction 0, 1, and 1.5% and the burning steady state temperature 500 and 600 °C. The specimens were divided into three groups, each group consists of three specimens. The specimens in the first group were tested with no fire effect to be the reference specimens, while the others of the second and third groups were tested after being exposed to fire-flame effect. The adopted characteristics of the fire test were; (one hour) burning time duration and 500 and 600 °C steady state temperature with sudden cooling process (water sprinkling directly after burning). The test results proved that exposing to direct fire effect for one hour caused a reduction in the punching shear strength with an increase in the ultimate mid-span deflection. Also, it was noticed that using steel fiber in the concrete mix leads to a significant increase in the punching shear strength for both the unburned and burned specimens. The ultimate punching load increased by about 11 and 16.6% for the unburned specimens with 1.0 and 1.5% steel fiber volume fraction, respectively, and by about 22.4 and 19% for the burned specimens at 500 °C with 1.0 and 1.5% steel fiber volume fraction, respectively. While, it was increased by about 29.2 and 21.5% for the burned specimens at 600 °C with 1.0 and 1.5% steel fiber volume fraction, respectively, as compared with the reference specimen of each group. Doi: 10.28991/cej-2021-03091751 Full Text: PDF